A Comprehensive Study on Metaverse and Its Impacts on Humans. (19th September 2022) - Bale, Ajay Sudhir; Ghorpade, Naveen; Hashim, Muhammed Furqaan; Vaishnav, Jatin; Almaspoor, Zahra
Abstract : Virtual Reality (VR) and Augmented Reality (AR) have revolutionized technology and taken the world by storm. They established the foundation for numerous future innovations. Virtual and augmented reality are now widely employed to improve user experiences in various areas. Over time, more and more companies and businesses have begun to use this cutting-edge technology to improve their products and services. Recently, the attention to VR and AR has exploded with the concept "Metaverse" surfacing in mainstream media. Many major companies have already set their goals in motion and are working on building the core of their metaverses. This review paper focuses on explaining the concept of the metaverse, its history, and its associated benefits. Through a survey, it helps understand people's concerns with the metaverse and how it can impact and affect humans mentally, physically, and psychologically. The analysis of this paper can help humans prepare themselves for what the new technologies have to offer, in addition to assisting companies in building a flawless metaverse.